(untitled) (Research, Society and Development, 2020)
This study aimed to make a diagnosis of the prevalence of dyslipidemia in children and adolescents in Brazil and check in the Base Nacional Comum Curricular (BNCC) if there is a suggestion to approach Brazilian schools on healthy living habits and health promotion. This research used a qualitative and quantitative approach of integrative review on lipid profile data available in theses and dissertations. The BNCC interpretative assessment was carried out by describing the skills and competences of the disciplines of Physical Education, Science and Biology to verify the presence of the theme health promotion and incite a reflection on ways of approaching this content in the country’s education system. The results demonstrate that the prevalence of dyslipidemia in children and adolescents is high, providing a potential risk for the development of cardiovascular disease in adulthood. In addition, the guidelines for guiding the topic in school settings occur discreetly and only after the age at which individual habits are already established. Therefore, this study shows the need for measures of early diagnosis, associated with programs for the prevention of dyslipidemia, and actions for education, awareness and the definition of public policies aimed at health promotion. And it suggests that scientific knowledge, linked to Science Education, can stimulate the students’ perception process about the importance of a physically active life routine and healthy eating habits, for health promotion.